Musculoskeletal Complaints among Itinerant Tailors in Lenteng Agung, Jakarta - Naufal Arya Putra Nurjaman; Yosua Novalesi; Yannes Martinus Pasaribu; Etika Vidyarini (Telkom University, 2025)
Itinerant tailors in urban Indonesia often work in prolonged static postures within mobile workstations lacking ergonomic support. This study examines the prevalence of musculoskeletal complaints and postural risks among 30 male itinerant tailors in Lenteng Agung, South Jakarta. Using a mixed-method approach, quantitative data were collected through the Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA), while qualitative insights were obtained via semi-structured interviews. Results showed that 100% of participants fell into high or very high ergonomic risk categories, with prevalent discomfort in the buttocks, lower back, and hips. No statistically significant correlation was found between age or work duration and complaint severity, indicating that workstation design plays a more critical role. Interview findings revealed self-adapted seating modifications and a strong demand for portable ergonomic improvements. The study highlights the urgent need for anthropometrically informed seating solutions compatible with mobile informal labor settings. These findings inform context-sensitive design strategies that prioritize adjustability, user comfort, and occupational health in underserved worker populations.